Proposal Allocation Ratio as a Moderator of Interpersonal Responsibility Effects on Hostile Decision-Making in the Ultimatum Game - Gong, Xinyu; Xia, Ling-Xiang; Sun, Yanlin; Guo, Lei; Carpenter, Vanessa C.; Fang, Yuan; Chen, Yunli (Frontiers in Psychology, 2017)
Interpersonal responsibility is an indigenous Chinese personality construct, which is regarded to have positive social functions. Two studies were designed to explore the relationship among interpersonal responsibility, proposal allocation ratio, and responders’ hostile decisions in an ultimatum game. Study 1 was a scenario study using a hypothetical ultimatum game with a valid sample of 551 high school students. Study 2 was an experimental study which recruited 54 undergraduate students to play the incentivized ultimatum game online. The results of the two studies showed a significantly negative correlation between interpersonal responsibility and responders’ rejection responses only when the proposal allocation ratio was 3:7. In addition, in study 2, interpersonal responsibility had negative effects on responders’ rejection responses under the offer of 3:7, even after controlling for the Big Five personality traits. Taken together, proposal allocation ratio might moderate the effects of interpersonal responsibility on hostile decision-making in the ultimatum game. The social function of interpersonal responsibility might be beyond the Big Five. Keywords: interpersonal responsibility, proposal allocation ratio, hostile decision-making, moderator, ultimatum game, Big Five personality